GAMBARAN PENGETAHUAN REMAJA PUTERI TENTANG KEPUTIHAN DI PESANTREN HASANATUL BAROKAH KECAMATAN TAMBUSAI - Erry Haryanti, Nana Aldriana, (Jurnal Martenity and Neonatal, 2018)
Fluor Albus is the discharge of dilute white fluid from the vagina. The incidence ofÂ Fluor Albus on women in the world in 2013 reached 75%, in Europe women have fluor albus of 25% and in Indonesia who experienced whiteness reached 75%. This study aims to determine the description of the knowledge of adolescent about Flour Albus in Pesantren Harianul Barokah Suka Maju Tambusai 2016. This research method is quantitative analytic with cross sectional design. Population and Sample in this research is all girl adolescent at Pesantren Hasanatul Barokah which amounted to 64 people. The type of data used is the primary data collected using questionnaires. Data analysis using univariate analysis. The result of the research on the level of knowledge of girl adolescent about flour albus in Pesantren Hasanatul Barokah in good category is 5 respondents (7,9%) enough category 11 respondents (17,2%) and less category is 48 respondents (74,9%). From the research results can be concluded the level of knowledge of Young Women About Whiteness in Pesantren Hasanatul Barokah is the majority less that is 48 respondents (74,9%). Suggestions for the school should be able to provide sources of information in the form of books, magazines or health articles related to leucorrhea in order to increase student insight about leucorrhoea. For Health Worker in order to give counseling to Pesantren Hasanatul Barokah and can know the problem that exist in boarding school.